Науково-культурне значення "Букваря южнорусского" Т.Шевченка і "Граматки" П.Куліша - Курабцева, І.К. (Кримський науковий центр НАН України і МОН України, 2004)
У статті вперше аналізується українська термінологія , яка вживалася в "Букварі южнорусском" Т.Г.Шевченка (1861р.) і "Граматці" П.Куліша (1857 р.). In this article the Ukrainian terms are analyzed for the first time. These terms were used in the Sauts-russian ABC book by T.G.Shevchenko and in the Grammar-book by P.Kulish.